2019
DOI: 10.1186/s40360-019-0285-y
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions associated with six commonly used antiepileptic drugs in southern China from 2003 to 2015

Abstract: BackgroundThis active, open observational study aimed to investigate adverse drug reactions (ADRs) associated with six commonly used antiepileptic drugs (AEDs) in southern Chinese outpatients with epilepsy from 2003 to 2015.MethodsThe Wenzhou Epilepsy Follow-Up Registry Database (WEFURD) was established by a single epilepsy center in China in January 2003 to record AED efficacy and the associated ADRs by registered outpatients diagnosed with epilepsy. We reviewed the data of outpatients who had only taken one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…Currently, antiepileptic drug (AED) therapy is the main treatment for epilepsy, and 65%‐85% of people with epilepsy (PWE) experience a long‐term seizure‐free period on medication . Nevertheless, nearly 60% of PWE experience adverse effects from AEDs that could result in a significant decline in the quality of life . In addition, PWE face a substantial economic burden because of the long‐term use of AEDs .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, antiepileptic drug (AED) therapy is the main treatment for epilepsy, and 65%‐85% of people with epilepsy (PWE) experience a long‐term seizure‐free period on medication . Nevertheless, nearly 60% of PWE experience adverse effects from AEDs that could result in a significant decline in the quality of life . In addition, PWE face a substantial economic burden because of the long‐term use of AEDs .…”
Section: Introductionmentioning
confidence: 99%
“…Considering that lower risks were associated with the use of LVT and TPM, which are both nonaromatic newer ASMs, the aromatic versus nonaromatic classification seems more important in predicting the development of SCARs due to ASMs compared to the old versus newer classification. Similarly, previous reports suggested that there is an increased risk of hypersensitivity when aromatic ASMs are used 3,7,18–20 . Aromatic ASMs commonly form metabolites known as “arene oxides,” and it has been hypothesized that this metabolite can act as a type of “hapten” that causes an immune response 3,18 .…”
Section: Discussionmentioning
confidence: 90%
“…However, ASMs cause adverse reactions in approximately 60% of the patients treated 3 . Specifically, aromatic ASMs are significantly associated with hypersensitive adverse reactions compared to nonaromatic ASMs 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that AEDs such as phenytoin and carbamazepine can only suppress the incidence of early PTE, but do not reduce the risk of late PTE, even during treatment [23, 24]. AEDs have some side effects, including psychiatric disorders, neurological disorders, gastrointestinal disorders, and skin and appendage disorders [25]. Nevertheless, due to the limitations of clinical treatment, AEDs remain the first choice for epilepsy treatment.…”
Section: Discussionmentioning
confidence: 99%